Florus' Vision of Rome - Gryksa, Edyta (Polskie Towarzystwo Filologiczne, 2018)
This paper is a summary of my PhD dissertation written under the supervision of Professor Anna Kucz (with Dr Patrycja Matusiak as auxiliary supervisor) and submitted to the Faculty of Philology of the University of Silesia in Katowice. The dissertation was reviewed by Professor Bogdan Burliga (University of Gdańsk) and Professor Marian Szarmach (Nicolaus Copernicus University in Toruń). The defence took place on 10 October 2016. The dissertation was published in Polish as: Edyta Gryksa, Obraz Rzymu u Florusa, Tarnów 2017.
Keywords: Florus; Rome